2022
DOI: 10.3389/fpubh.2022.912946
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review on population-centered indicators for cancer care continuum

Abstract: PurposeThe purpose of this study was to develop prioritized cancer indicators and measure the population-based monitoring of the entire life cycle of cancer care, guiding the improvement of care delivery systems.MethodsScoping review was performed based on the Joanna Briggs Institute's methodology. Electronic databases were searched in PubMed, Cochrane Library, EMBASE, Ovid Medline, RISS, KISS, and KoreaMed. The searches were limited to articles published in English between 2010 and 2020. No restrictions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…[3][4][5][6] Within the field of oncology, several QIs are used to assess quality of care along the cancer care continuum, from cancer screening to survivorship care. 7 By establishing tumor-site specific, evidence-based benchmarks in cancer care delivery, QIs can help identify gaps in healthcare delivery, patient experience and outcomes. Furthermore, they allow for comparisons over time within and between institutions, which inform areas of priority for organisations and accountability for quality improvement through targeted allocation of resources.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…[3][4][5][6] Within the field of oncology, several QIs are used to assess quality of care along the cancer care continuum, from cancer screening to survivorship care. 7 By establishing tumor-site specific, evidence-based benchmarks in cancer care delivery, QIs can help identify gaps in healthcare delivery, patient experience and outcomes. Furthermore, they allow for comparisons over time within and between institutions, which inform areas of priority for organisations and accountability for quality improvement through targeted allocation of resources.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Reviewing these two medical conditions provided an in-depth understanding of quality measures that should be monitored in a wide range of medical conditions (Kanaoka et al, 2022;Aktaa et al, 2022;Rajaguru et al, 2022). The evidence included in Chapter 2 revealed that measures of survival and disease control are commonly used in VBHC.…”
mentioning
confidence: 99%